Irrigation and Drainage Recent Advances - Sultan, Muhammad; Ahmad, Fiaz (IntechOpen, 2023)
Uneven distribution and depletion of good-quality water reserves significantly devastate the agriculture sector. In this scenario, water management as well as efficient irrigation and drainage strategies are primarily required to conserve water resources and enhance farm efficiency. Irrigation and Drainage - Recent Advances provides insights into irrigation methods, scheduling possibilities, and optimal irrigation frequencies. It also discusses management strategies including methods of groundwater recharging and rainwater harvesting, restoration, and modification of drainage networks for manifesting the cropping index. The book presents key aspects and examines the role of Agrovoltaic energy, artificial intelligence, and the Internet of Things (IoT) in the development of smart irrigation systems for sustainable farming.